RANCANG BANGUN ALAT PENDETEKSI LOGAM PADAT BERBASIS ARDUINO - Sakban, Muhammad; Tuty; Suharjo (Akademi Manajemen Informatika dan Komputer PARBINA NUSANTARA Pematangsiantar, 2025)
Technological developments are increasingly rapid, especially in the field of electronics. But with the rapid development of technology, we as humans have become dependent on this technology, one of which is a detector metal detection device. This metal detector is used to detect and identify metals in the ground surface. Here are some of the uses of meta detectors such as metals, tima and gold, at this time there is still a lot of metal or historical relics that have not yet been discovered, especially in Logas Village, Kuantan Singing Regency, with the existence of metal detectors can help people find back the history that has been buried in the ground, from the results of testing, this detection device or meta detector has successfully detected and marked the presence of metals in or above the ground surface.